Understanding accounting information system and its components: the case of a well established grocery chain in rural of Malaysia - Zainol, Zaini; Rasidi, Afiqah; Hamzah, Hanisah; Mamat zambi, Syafiqah (2014)
The main aim of this teaching case is to gain knowledge on the accounting information system being used in a retail industry for capturing business transactions namely sales, purchases and inventory. It was also to record nature of operational activities, documents, journals, controls, type of system used and the flow of accounting data in the chosen organization. Students were expected to conceptualize the actual system by using graphical documentation techniques such as data flow diagrams, flowcharting, and, research, events and entity (REA) diagram.